Design of liquid crystals with 'de Vries-like' properties: structural variants of carbosilane-terminated 5-phenylpyrimidine mesogens. Issue 18 (18th April 2017) - Schubert, Christopher P. J.; Müller, Carsten; Bogner, Andreas; Giesselmann, Frank; Lemieux, Robert P.
Abstract : Comparative analysis of linear and branched tricarbosilane terminated 'de Vries-like' mesogens. Abstract : Structural variants of the 'de Vries-like' mesogen 5-[4-(12, 12, 14, 14, 16, 16-hexamethyl-12, 14, 16-trisilaheptadecyloxy)phenyl]-2-hexyloxypyrimidine (QL16-6 ), including two isomers with branched iso-tricarbosilane end-groups, were synthesized and their mesomorphic and 'de Vries-like' properties were characterized by polarized optical microscopy, differential scanning calorimetry, small angle and 2D X-ray scattering techniques. A comparative analysis of isomers with linear and branched tricarbosilane end-groups shows that they exhibit comparable mesomorphic and 'de Vries-like' properties. Furthermore, the difference in effective molecular length L eff between the linear and branched isomers in the SmA and SmC phases ( ca. 4–5 Å), which was derived from 2D X-ray scattering experiments, suggests that the linear tricarbosilane end-group is hemispherical in shape on the time-average, as predicted by a DFT conformational analysis at the B3LYP/6-31G* level.